2008
DOI: 10.1068/a39203
|View full text |Cite
|
Sign up to set email alerts
|

Rescaling Employment Relations: Key Outcomes of Change in the Privatised Rail Industry

Abstract: IntroductionThe emergence of more flexible and contingent forms of employment has been a key outcome of wider processes of economic restructuring in recent decades, often framed in terms of increased globalisation and the collapse of the Fordist production system that characterised the postwar era (Herod et al, 2003;Rutherford and Gertler, 2002). Neoliberal policies of market liberalisation and deregulation have been an important influence on the restructuring of employment relations through the removal of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…, it often appears as a centre of crisis in mature 'developed' regions at least in the early 21 st century, with the economic and social landscape of cities in the 'developed' world having being transformed in recent decades by the processes of globalisation, technological change, deindustrialisation and tertiarisation (Sassen, 2006;MacKinnon et al, 2008). This sense of 'cities in crisis' predated the most recent financial crisis and credit crunch that has engulfed much of the world, with the latter exposing further the more deep-seated structural and strategic issues facing our cities.…”
mentioning
confidence: 99%
“…, it often appears as a centre of crisis in mature 'developed' regions at least in the early 21 st century, with the economic and social landscape of cities in the 'developed' world having being transformed in recent decades by the processes of globalisation, technological change, deindustrialisation and tertiarisation (Sassen, 2006;MacKinnon et al, 2008). This sense of 'cities in crisis' predated the most recent financial crisis and credit crunch that has engulfed much of the world, with the latter exposing further the more deep-seated structural and strategic issues facing our cities.…”
mentioning
confidence: 99%
“…Furthermore, some researchers recounted labour unions’ activities, for example the fact that the majority of strike action has been conducted against particular operators at the local and regional levels, reflecting the logic of company‐level bargaining (e.g. MacKinnon et al ., ), and trade unions are taking action against liberalization and privatization, as these are perceived as representing a threat to workers (e.g. Schulten et al ., ).…”
Section: Modelmentioning
confidence: 99%
“…Bridge (2008, 87-89, emphasis in the original) suggested that economic geographers should combine their efforts to understand "the difference that 'environment' makes to processes we have traditionally considered to be (purely) economic." Indeed, in the context of resource development, analyses of bargaining that have emphasized conflicts between multinational corporations (MNCs) and governments (Kobrin 1987) and between business and labor (Holmes 2004;MacKinnon, Cumbers, and Shaw 2008) need to give priority to the role of ENGOs. Martin 2001;McCarthy 2002;Walker 2003;Environment and Planning A 2005;Geoforum 2006) and related literatures (e.g., Clapp 2004;Hayter 2003).…”
Section: Environmental Bargainingmentioning
confidence: 99%
“…Context-sensitive and actor-centered approaches that stress the importance of "micropolitics," local histories and traditions to resource claims, as well as their interpretations, integrate different scales of analysis to explain localized conflicts, such as the disenfranchisement of local uses through international economic interests. Indeed, in the context of resource development, analyses of bargaining that have emphasized conflicts between multinational corporations (MNCs) and governments (Kobrin 1987) and between business and labor (Holmes 2004;MacKinnon, Cumbers, and Shaw 2008) need to give priority to the role of ENGOs. Research has been conducted on the influence of international ENGOs on MNCs and governments, particularly with respect to globalization (e.g., Doh andTeegen 2002, 2003;Teegen 2003).…”
Section: Environmental Bargainingmentioning
confidence: 99%